2007
DOI: 10.1016/j.vetimm.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the probiotic Bacillus cereus var. toyoi on the intestinal immunity of piglets

Abstract: In a feeding trial, sows and piglets were fed with the probiotic bacterium Bacillus cereus var. toyoi as a feed additive, and the effects on immune cell populations were examined. The development of the gut immune system was determined for piglets at the ages of 14, 28, 35 and 56 days post partum. Tissue samples of the Jejunum and the continuous Peyer's patch were used for enumeration of intraepithelial lymphocyte populations by fluorescence activated flow cytometry and fluorescence microscopy. Both independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 33 publications
5
41
0
2
Order By: Relevance
“…Multiple studies have confirmed the stimulating effects of probiotics on the intestinal environment (Barrow et al, 1977;Roth et al, 1992b; Depta et al, 1998;Mathew et al, 1998;Jadamus et al, 2001;Scharek et al, 2005Scharek et al, , 2007Reiter et al, 2006;Lodemann et al, 2008). By lowering the pH value in the small intestine and producing organic acids and antibacterial substances probiotic supplements inhibit pathogenic microorganisms, improve the intestinal microflora and stimulate immune function (Kumprecht et al, 1994;MantereAlhonen, 1995;Marinho, 2007).…”
Section: Probioticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple studies have confirmed the stimulating effects of probiotics on the intestinal environment (Barrow et al, 1977;Roth et al, 1992b; Depta et al, 1998;Mathew et al, 1998;Jadamus et al, 2001;Scharek et al, 2005Scharek et al, , 2007Reiter et al, 2006;Lodemann et al, 2008). By lowering the pH value in the small intestine and producing organic acids and antibacterial substances probiotic supplements inhibit pathogenic microorganisms, improve the intestinal microflora and stimulate immune function (Kumprecht et al, 1994;MantereAlhonen, 1995;Marinho, 2007).…”
Section: Probioticsmentioning
confidence: 99%
“…Intestinal microflora can be modulated by the supplementation of feeds with probiotic bacterial species of the genera Lactobacillus, Bifidobacterium (Bomba et al, 1998), Bacillus (Roth et al, 1992b;Alexopoulos et al, 2001;Scharek et al, 2005Scharek et al, , 2007, Enterococcus and Streptococcus (Scharek et al, 2005(Scharek et al, , 2007 and their combinations (Mathew et al, 1998;Bomba et al, 2002). The bacteria Enterococcus faecium were found to be able to prevent the K88 Table 2.…”
Section: Probioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…For enumeration of intraepithelial lymphocyte population fluorescence activated flow cytometry was applied, in some cases expanded by fluorescence microscopy. The detailed results are documented in several publications (Scharek et al, 2005(Scharek et al, , 2007bSchierack et al, 2007Schierack et al, , 2009. Following only some of the main findings are summarized.…”
Section: Resultsmentioning
confidence: 99%